The Role of Baitul Maal Wa Tamwil in Encouraging MSMEs in Sukabumi District (Field Study at BMT Ibadurrahman Sukabumi City) - Neni Nuraeni; Evi Sopiah (Al-Muamalat, 2023)
BMT Ibadurrahman is an economic and financial institution that applies Shariah principles in all its activities. The main target of BMT Ibadurrahman is micro, small, and medium enterprises abbreviated as MSMEs. The empowerment of MSME actors is one of the patterns of creating distributive justice patterns in the Islamic economy. In addition to creating distributive justice in the economy, making people aware of the dangers of usury is one of the objectives of BMT Ibadurrahman's presence in order to prevent people from getting involved in the vicious practice of usury. The empowerment pattern carried out by BMT Ibadurrahman is not so smooth because there are several things that need to be prepared. There are two factors that are one of the causes of obstruction of the MSME empowerment pattern carried out by BMT Ibadurrahman, both from internal and external perspectives. This is an obstacle for BMT Ibadurrahman in achieving the empowerment of MSMEs in Sukabumi City and Sukabumi Regency.